Motor Development in Children With Autism Spectrum Disorder - Mohd Nordin, Ashikin; Ismail, Juriza; Kamal Nor, Norazlin (Frontiers in Pediatrics, 2021)
Objective: This study was conducted to determine the gross and fine motor profiles of children with autism spectrum disorder compared to typically developing children. Additionally, we also assessed if the motor delay was more pronounced with increasing age. Method: This was a retrospective study involving children aged 12 to 60 months of age comparing motor development in children with autism spectrum disorder with typically developing children. Their developmental profile was assessed using Schedule of Growing Skills II. Descriptive statistics was used to analyse the developmental profile between the groups. Results: ASD children had significant gross motor (6.7%) and fine motor delay (38.5%) compared to typically developing children, who did not show any delay. The motor delay in ASD children was more prominent in older children. Conclusion: It is important to assess motor development in ASD children as there is significant motor delay in these children compared to typically developing children, and the delay becomes more prominent with age. Early detection of motor delay could allow provision of early intervention services to optimize developmental outcomes.